The Perspective of Community Voice and Islamic Law on Akad Bhekal Tradition in Maron Kidul, Probolinggo District: Tradisi Akad Bhekal di Desa Maron Kidul Perspektif Masyarakat Dan Hukum Islam - Linda Ruzyanti; Abu Yazid Adnan Quthny; Imam Syafi’i (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
The bekalan tradition frequently becomes the topic of discussion in the social community. The initial purpose of holding the bekalan tradition, which should be a pattern of intimacy, has now become a common mistake. Some associations between men and women during bhekalan are often known to deviate from Islamic Law. It has become standard when it is known that men and women during Bhekalan are always together, holding hands and even staying at their partner's house. Ironically, if such things are not done, it becomes a topic of controversy in the neighbourhood. The research discussed the implementation of the akad bhekal tradition that occurs in the Maron Kidul community and the community's perspective and Islamic Law on the tradition. It occurs due to the community's traditional law, which appears to have taken the form of local community customary law. This research uses a qualitative method where the primary source is obtained through observation, interview and documentation. The technique of testing data validity is to use the triangulation method. This research shows that the tradition of akad bhekal is not a fixed tradition that applies to the entire village of Maron Kidul. Furthermore, the implementation of the Akad Bhekal is the same as the implementation of the Akad Sirri.